Neurociênia, educação e a formação de professores: a percepção sobre origem e aceitação de neuromitos entre licenciados em Ciências da Natureza - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Neuromyths are mismatched information about brain functioning, supposedly based on scientific research. Its approach to Education has grown in recent decades with the expansion of Cognitive Neuroscience, arousing the interest of teachers, teachers in training and the community in general. The receptivity presented can negatively influence their practices and knowledge in relation to teaching and learning because they are vulnerable to the bombardment of information circulating in popular media and the lack of specific knowledge. Based on this information, the present research aims to characterize the profile of the incidence of neuromyths among undergraduate students in the areas of Natural Sciences, as well as their origins and implications. It is a qualitative research with a methodological approach of quantitative and qualitative analysis. Participants are graduates of Biology, Physics and Chemistry courses at the State University of Ponta Grossa, Paraná. Data collection consisted of two stages: 1) questionnaire via online form (N = 33); and 2) semi-structured interview (N = 11). For the treatment of the data, the Percentage Descriptive Analysis was used for the objective questions, while the Textual Discursive Analysis and Cluster Analysis was used in the rest of the data, in which it became possible to identify five clusters, that is, five groups of licensors as their similarities and dissimilarities, in relation to their perceptions about neuromyths. The results showed that regardless of the school trajectory, course, gender and school period, there is a belief among the undergraduate students in most of the ten neuromyths discussed, and a low belief in only two, but their statements demonstrate that there is confusion regarding the application of such knowledge and agreeing or ignoring neuromyths are not significantly different in terms of the implications related to them. Such results are in line with research already carried out in other countries and these assumptions allow us to affirm that there is a common culture shared among these undergraduates that has been outlined throughout their trajectories, whether through the media, social media or educational path, since the Basic Education to Higher Education, indicating the need for Scientific Literacy related to Neuroscience and an evidence-based education.
Keywords: Neurociência; Educação; Formação de Professores; Neuromitos; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA